Honey Analysis 2017
DOI: 10.5772/66328
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Procedures for Determining Heavy Metal Contents in Honey: A Bioindicator of Environmental Pollution

Abstract: Metals are pollutant residues detectable in honey and in fact account for most of the inorganic pollutants found in this food product. Metal pollutants can be accumulated through the food chain and, at levels exceeding safe thresholds, can be toxic to humans and even damage physiological functions. During the honey-making process, bees can transport pollutants to the beehive following contact with polluted botanic species or from drinking contaminated water. Detecting very low concentrations is a persisting ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The presence of heavy metals in foodstuffs is becoming increasingly more obvious and food consumption represents the main way of access to the human body [1,2] with potentially negative effects on human health, especially because heavy metals de-regulate the immune system [3] and lead to severe diseases, including cancer, cardiovascular diseases, and neurological disorders [4][5][6]. Heavy metals persist and biomagnify in trophic chains, and when in concentrations above the maximum permissible limits, they become toxic [7]. High concentrations of heavy metals pose a risk to consumer health, while prolonged consumption of honey containing Cu and Fe causes gastrointestinal disorders [8].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of heavy metals in foodstuffs is becoming increasingly more obvious and food consumption represents the main way of access to the human body [1,2] with potentially negative effects on human health, especially because heavy metals de-regulate the immune system [3] and lead to severe diseases, including cancer, cardiovascular diseases, and neurological disorders [4][5][6]. Heavy metals persist and biomagnify in trophic chains, and when in concentrations above the maximum permissible limits, they become toxic [7]. High concentrations of heavy metals pose a risk to consumer health, while prolonged consumption of honey containing Cu and Fe causes gastrointestinal disorders [8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies showed that the inorganic content is not dependent on the botanical origin, but rather on the composition of the soils and water in the areas surrounding beehives, and other environmental conditions play an important role in this case [10,22]. Also, honeys that contained metals in their composition showed a decreased antioxidant activity compared with control samples [23]. The same trend was found in bee pollen samples obtained from the same beehives [24].…”
Section: Undesirable Residuesmentioning
confidence: 68%
“…Solid phase extraction by the use of mineral acids can be advantageous because it destroys all of the organic matter present in the matrix of honey, thereby reducing analysis time and risks of analyte loss that could affect result reliability, while in calcination procedures, the prevention of losses in the interior of the muffle furnace can be a complex process to regulate, directly affecting the distribution of the data obtained and the variability in the response. Then, these variations constitute another challenge during calcination via a muffle furnace [12]. The determination of inorganic components of honey by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) is useful considering the multielement characteristics that permit a rapid analysis, with good precision and accuracy, but, honey is a complex matrix highly rich in organic matter and different strategies for sample treatment have been proposed [29].…”
Section: Selection Of Honey Pretreatment Strategymentioning
confidence: 99%
“…Additionally, the study in all commercial honeys was carried out for Pb, As, Hg, Cd but were not detected. The presence of metals in honey has been linked with the existence of hives close to contamination sources, such as factories, highways, volcanoes, or mines/mine tailings, even pollution sources can also comprise agrochemicals that contain cadmium and arsenic, among others [12,39].…”
Section: Analysis Of Mineral Composition In Artisanal and Commercial mentioning
confidence: 99%